Stanovanjske strategije in stanovanjski trg v Ljubljani - Cirman, Andreja (Urbani izziv, 2007)
Mobility of households has positive effects on a macro level, as it is linked to the optimal distribution of household in the housing fund and indicates an equilibrium of supply and demand. In the article housing strategies of household in city of Ljubljana are presented. Special emphasis is given to theeconomic status and financial ability of households (for moving). Through this the authors try to discern how well the housing market in Ljubljana is functioning. Furthermore, past and future financial strategies of movers are analysed and on the basis of this analysis future needs of households are identified. In the conclusion the authors present some possible measures to aid households and promote housing mobility and (consequently) also housing conditions of inhabitants of Ljubljana. The data source is Housing survey 2005.
Keywords: Ljubljana; stanovanja; stanovanjska politika; stanovanjski trg; strategija